High heels and high tempers : a study into female violence - Williams, Sarah (2012)
This thesis provides a critical account of a small-scale study into women who perpetrate verbal, physical and sexual violence towards intimates, acquaintances and strangers of both sexes. The sample was mainly taken from two sources in West Yorkshire: a women's self-help perpetrator counselling group (S.T.O.P), and a women's centre which provides support for females with a history of offending or at risk of offending (the Together Women Project). Using qualitative data collected from anger management group observations and in depth interviews with eighteen female perpetrators and eleven key informants who have come into contact with violent women, this study affords a voice for female perpetrators, whose perspectives and experiences are often overlooked in the UK. This thesis examines the ways in which violent women are understood; not only in terms of how perpetrators understand their own violent behaviour and violent identities, but how others who work with violent women comprehend and problematise such behaviour. This study analyses the nature and character of female violence and investigates the impact of violence upon the lives of perpetrators. It also investigates what influence anger management 'treatment' has upon the relationships and behaviours of violent women. Aware that respondent's understandings of violence are influenced by the matrix of care and control that surrounds them, this study explores the ways in which participants struggle to retain and articulate 'their' own definitions of violence. Findings reveal that some respondents in this study utilised power and control towards both male and female opponents when using violence. Violence was often calculated and rational; for some interviewees it provided great enjoyment, power and a sense of identity. As the issue of female violence is such an under researched topic, these findings not only add an original contribution to the current literature, they sometimes contradict long-standing theories which surround gender identities and violence as a whole